Evaluasi Ketepatan Saran Waktu Penyimpanan yang Tercantum dalam Label Kemasan Produk Daging - Kiyat, Warsono El (Surya Octagon Interdisciplinary Journal of Science and Technology, 2018)
Food shelf life can be determined by the critical factors that are most rapidly deteriorated. It can be evaluated by using Arrhenius method. This study aimed to determine the basis used by a company in evaluating the shelf life of food products. Observations were carried out on processed beef products sold in supermarkets in Bogor. Samples studied were meatballs, sausage, and beef burgers purchased from supermarkets under various trademarks. The calculation of shelf life was mathematically carried out by Arrhenius method that was through the measurement of the rate of quality parameter degradation. The results showed that Arrhenius model could be used to measure the rate of quality reduction of meatballs, sausage, and burger meat products so it could be predicted the shelf life of the product. The assumption used by the producers was quite appropriate because it was in accordance with the Arrhenius method.